2009
DOI: 10.1111/j.1600-6143.2009.02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Circulating Antibody Levels Induced by ABO Antibody Adsorption for ABO-Incompatible Kidney Transplantation

Abstract: ABO-incompatible kidney transplantation using immunoadsorption to remove anti-A/B antibodies has become a successful clinical practice. Since the data on the specificity of the ABO columns are controversial, the present study assessed the efficiency and specificity of the ABO immunoadsorption, the effect on total immunoglobulins and antibodies previously induced by vaccination. Anti-A/B antibodies were measured by agglutination and ABO flow cytometry, total IgG/IgM, carbohydrate-and protein-specific antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
(119 reference statements)
2
32
0
3
Order By: Relevance
“…Die Antikörperelimination erfolgt mittels antigenspezifischer IA unter Verwendung der Glycosorb ® -AB0-Säule (Glycorex Transplantation, Lund, Schweden). Bei der Glycosorb ® -AB0-Säule handelt es sich um eine Einmalsäule, die effektiv spenderspezifische Anti-A-oder Anti-B-IgG-und -IgM-Blutgruppenantikörper mit einer Absenkrate von 56 beziehungsweise 81 % während der ersten Behandlung eliminiert [10]. Das sowohl für die Desensibilisierung bei Blutgruppeninkompatibilität als auch zur Elimination von HLA-Antikörpern eingesetzt werden kann ("Onesize-fits-all"-Protokoll, Abb.…”
Section: Ab0-inkompatible Nierentransplantationunclassified
“…Die Antikörperelimination erfolgt mittels antigenspezifischer IA unter Verwendung der Glycosorb ® -AB0-Säule (Glycorex Transplantation, Lund, Schweden). Bei der Glycosorb ® -AB0-Säule handelt es sich um eine Einmalsäule, die effektiv spenderspezifische Anti-A-oder Anti-B-IgG-und -IgM-Blutgruppenantikörper mit einer Absenkrate von 56 beziehungsweise 81 % während der ersten Behandlung eliminiert [10]. Das sowohl für die Desensibilisierung bei Blutgruppeninkompatibilität als auch zur Elimination von HLA-Antikörpern eingesetzt werden kann ("Onesize-fits-all"-Protokoll, Abb.…”
Section: Ab0-inkompatible Nierentransplantationunclassified
“…A1 and A2 blood group antigens differ qualitatively and quantitatively (see above). Indeed, for transplantation from A2 donors into B or O recipients, anti-A1 IgG titers that were above 1:128 have been shown to represent a significant risk factor for AMR (Squifflet et al, 2004;Tyden et al, 2010;Valli et al, 2009;Warren et al, 2004). In addition, Alkhunaizi reports that up to 8% of A2 individuals have anti-A1 IgG antibodies in their sera (Alkhunaizi, 2006).…”
Section: The Removal Of Anti-ab Blood Group Antibodiesmentioning
confidence: 99%
“…For example, the A blood group antigen has higher expression levels than the B blood group antigen. Interestingly, immunohistochemical analysis has revealed that the A2 blood group has the lowest cell surface expression (Pober et al, 1997;Shimmura et al, 2004;Yung et al, 2007); however, data analysis of kidney transplants that has been performed across ABO barriers has not revealed statistically significant differences between the A (donor) →B (recipient) or B (donor) →A (recipient) groups (Squifflet et al, 2004;Sugiyama et al, 2005;Valli et al, 2009). …”
Section: Antibodies Against a And B Blood Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to plasmapheresis, immunoadsorption method can selectively remove anti-ABO antibodies, unaffecting the levels of the other plasma proteins. The blood type-specific columns can effectively remove anti-A or anti-B antibodies, and approximately 30% of anti-A/B IgM and 20% of anti-A/B IgG levels can be removed after a single treatment (Valli et al, 2009). In spite of its physiologic technique and successful clinical applications, the high cost of immunoadsorption column is a major limiting factor blocking its widespread use.…”
Section: Antibody Reduction Therapiesmentioning
confidence: 99%